The effect of indium-tin oxide coatings on the formation of craters on glass surfaces under the impact of high-velocity microparticles; Acta Astronautica; Vol. 204 - Tursunkhanova R. Ryskul; Sergeev V. P. Viktor Petrovich; Kalashnikov M. P. Mark Petrovich; Sergeev O. V. Oleg Viktorovich; Neyfeld V. V. Vasily Viktorovich (2023, 2023)
Title screen